Utilization patterns and prescription characteristics of traditional Chinese medicine among patients with irritable bowel syndrome in Taiwan - Gu, Ye; Lai, Yu-Tung; Chang, Fang-Rong; Chen, Chung-Yu (Frontiers in Pharmacology, 2023)
Background: Few studies have investigated traditional Chinese medicine (TCM) utilization patterns for irritable bowel syndrome (IBS), despite the potential benefits of exploring TCM utilization patterns in optimizing TCM management. This study aimed to evaluate TCM utilization patterns and clinical features for IBS patterns in Taiwan. Methods: This was a population-based cross-sectional study using claim data from the National Health Insurance Research Database between 2012 and 2018. Patients newly diagnosed with IBS and aged over 20 years were included. The TCM utilization patterns and characteristics, including Chinese herbal medicine (CHM) treatment types and prescription patterns, were evaluated. Results: A total of 73,306 patients newly diagnosed with IBS used TCM for IBS at least once. Females used TCM for IBS more than males (female-to-male ratio = 1.89 : 1). The age distribution showed a peak at 30–39 years (27.29%), followed by 40–49 years (20.74%) and 20–29 years (20.71%). Patients who received Western medications for IBS had a lower tendency to seek TCM. CHM was the most commonly used TCM modality (98.22%), with Jia-wei-xiao-yao-san being the most commonly prescribed Chinese herbal formula and Bai-zhu being the most frequently prescribed single Chinese herb. Conclusion: This study enhances our understanding of TCM usage patterns for IBS, particularly CHM prescriptions. Further research is needed to investigate commonly used TCM formulas and individual herbs. Keywords: traditional Chinese medicine, irritable bowel syndrome, Chinese herbal medicine, utilization patterns, real-world data